(untitled) (Práxis Educativa, 2009)
This article analyzes the perceptions of municipal school principals in a city of the state of São Paulo concerning the implementation of the nine-year-long elementary education system. The data collection instruments included semi-structured interviews with the city’s chairman of the Board of Education as well as with principals and vice principals. The researchers considered city and state legislation, identified the main guidelines proposed by municipal professionals and also the difficulties and victories experienced by city schools. The highlights of the results found a positive perception by professionals of the established Educational Policy. The major problems pointed out in the interviews refer to the operational and technical issues rather than on political choice. Keywords: School Organization. Elementary School. School management.